Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3144/expresspolymlett.2009.51
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide/silica hybrids via the sol-gel route: High performance materials for the new technological challenges

Abstract: Abstract. The present review article describes in detail the state-of-the-art of organic-inorganic hybrid materials based on polyimide/silica components. The article is divided in three parts. In the first the basic processing route for the preparation of these systems is described, i.e. the sol-gel technique, along with the strategies developed to control the final morphology. In the second part the curing characteristics, the dynamic-mechanical and the mechanical and fracture properties of hybrids with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 74 publications
(115 reference statements)
3
19
0
Order By: Relevance
“…The synthesis of polyimide-silica hybrid materials and the investigation of their physical and gas transport properties have also received much attention. [9][10][11]. In previous researches, we found that the gas permeability and CO 2 /CH 4 selectivity of these membranes prepared via sol-gel reaction using tetramethoxysilane (TMOS) increased with increasing silica content, suggesting the characteristic distribution and interconnectivity of free volume holes created by the incorporation of silica [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of polyimide-silica hybrid materials and the investigation of their physical and gas transport properties have also received much attention. [9][10][11]. In previous researches, we found that the gas permeability and CO 2 /CH 4 selectivity of these membranes prepared via sol-gel reaction using tetramethoxysilane (TMOS) increased with increasing silica content, suggesting the characteristic distribution and interconnectivity of free volume holes created by the incorporation of silica [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, an excellent porous polymer matrix should satisfy a variety of requirements, such as desirable thermal stability, chemical resistance and high modulus to support the void structure. Polyimide (PI) is considered as the most promising candidates that could satisfy the above requirements with high thermal stability, good mechanical properties, excellent adhesion properties and outstanding dimensional stability [5][6][7]. Up to now, several studies have been contributed to the preparation of well-defined porous PIs, such as PI membranes and PI foams; however, few reports have focused on preparing porous PI microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an important advantage of the sol-gel synthesis route for polyimide/silica hybrid is that the poly(amic acid) organic matrix acts to prevent agglomeration of the silica, which can induce to nanometer scale silica clusters in the hybrids [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%